Upaya Berbasis Masyarakat Untuk Pencegahan Stunting Dengan Pemberdayaan Kader Untuk Stimulasi Pertumbuhan Dan Perkembangan - Annisa, Rahma; Wijaya, Andra Saferi; Elly, Nur; Idramsyah, Idramsyah (Borneo Community Health Service Journal, 2024)
Prevention of stunting is a priority development program in Indonesia until 2024. Nutrition in the first 1000 days of life (HPK), which is from the fetus is in the womb until 2 years old, is very important to consider as an effort to prevent the risk of stunting. Health cadres play an important role in self-care management of maternal nutrition during pregnancy as an effort to prevent stunting. The problem faced by health cadres in Talang Benuang Village and Lokasi Baru Village of Air Priukan Subdistrict as a village of 20 special locations (locus) for stunting in Seluma Regency in 2020 is a lack of knowledge about stunting and 1000 HPK so that they do not have sufficient provisions to carry out their role as perpetrators driving the community in realizing health, including the prevention and management of stunting. The goal of PKM is to empower cadres as the front guard in improving nutrition self-care management for pregnant women to minimize the risk of stunting in children under five. The method was to conduct socialization, training, and mentoring cadres in self-care management of nutrition for pregnant women. The result of the activity was an increase in knowledge, skills, and independence of cadres in providing education and assistance to pregnant women in nutrition management self-care. Cadres were expected to apply the knowledge and abilities they have acquired to provide education and assistance to pregnant women in their area. Counseling has proven effective in increasing understanding of parents and cadres regarding stunting. Parents and cadres responded enthusiastically to the material because they gained new knowledge. Therefore, it is necessary to increase socialization and training activities for parents and cadres. Based on the monitoring and evaluation that has been carried out by the implementation team, the recommendation for the follow-up plan proposed by the team is that similar activities must be carried out continuously in the context of health promotion for the elderly.